E-SCRAPBOOK IN CASE STUDY-BASED LEARNING: A METHOD TO IMPROVE STUDENTS' CRITICAL THINKING - Dotrimensi, Dotrimensi; Mustika, Maryam; Ikbal, Asep (JURNAL NALAR PENDIDIKAN, 2024)
In the 21st century digital era, technological advancements have significantly impacted education, demanding critical thinking skills to support students' career and life development. This study aims to examine the application of e-scrapbooks in case-based learning as a method to enhance students' critical thinking skills. The research uses action research with a qualitative approach, analyzed through the Spiral Model of Kemmis and Taggart. The subjects were 86 students enrolled in the Basic Social and Cultural Sciences course. Results showed that students, when creating e-scrapbook content, identified relevant issues in education, society, and culture, formulated questions, and analyzed cases. They then sourced, reduced, and evaluated the credibility of data before presenting, revising based on feedback, and consulting with lecturers. A questionnaire indicated a 77.71% positive response, categorized as "Good," confirming that case-based e-scrapbook creation effectively enhanced students' critical thinking skills.